KAJIAN PEMANFAATAN TANAMAN OBAT SEBAGAI ANTIDIABETES ALAMI - Syahputri, Eka Qurniati; Riyanti, Soraya (LPPM Universitas Bina Bangsa, 2024)
Diabetes mellitus (DM) is the most common chronic disease worldwide characterized by elevated blood glucose levels from normal values of > 126 mg/dl with a high prevalence that requires ongoing treatment. The use of antidiabetic drugs can cause side effects in long-term use.Indonesia has enormous natural wealth, plants with medicinal properties as natural ingredients have been utilized by the community since long ago. The preparation of this narrative review article was carried out through a literature search using the search engines Google Scholar, PubMed, Research Gate, Science Direct berISSN, SINTA accredited and international journals. The results of the literature study obtained 59 articles showing several families identified and reported to have activity as antidiabetics including Zingiberacecae, Rubiaceae, Caricaceae, Malvaceae, Phyllanthaceae, Verbenaceae, Lythraceae, Myrtaceae, Cucurbitaceae, Moringaceae, Asteraceae, Clusiaceae, Acanthaceae and Moracecae. Based on literature searches, many plants can be used as alternatives in the treatment of diabetes of course with the right dose and processing methods